The effects of leadership styles of healthcare institutionmanagers on the job satisfaction and organizationalcommitment of healthcare workers - AKYURT, NURAN (My University, 2024)
In this study, it is aimed to reveal the effects of the leadership styles of the managers in health institutions on the job satisfaction and organizational commitment of the employees. The data necessary for the research, a survey was conducted among 140 medical professionals working in the administrative departments of hospitals on the Anatolian side of Istanbul with bed capacity of 600 and more. The first section of the study consist of the factor analysis of the measurement instruments of job satisfaction, organizational commitment, and five leadership behaviours. Kaiser-Meyer-Olkin (KMO) test, and the Bartlett’s Sphericity test showed that the study sample was appropriate for the factor analysis. The second section includes multivarite regression model and the univarite analysis. The descriptive statistics of the participant characteristics, and the scales were presented with mean and standard deviation, and frequencies and percentage. The statistical significance was at 0.05 level. The exploratory variables were the participant charactersitics, and the leadership behaviours that found to have statistically significant relationship with the dependent variables. As a result, it is supported by our research findings that the organizational commitment of the personnel working in healthcare institutions is related to the concepts of taskoriented leader and people-oriented leader. Keywords: Health professional, Job satisfaction, Leadership, Organizational commitment.

Bu çalışmada sağlık kurumlarında görev yapan yöneticilerin liderlik tarzlarının çalışanların iş tatmini ve örgütsel bağlılıkları üzerindeki etkilerinin ortaya konulması amaçlanmaktadır. Gerekli verilerin toplanması amacıyla İstanbul Anadolu yakasında yatak kapasitesi 600 ve üzeri olan hastanelerin idari bölümlerinde görev yapan 140 sağlık çalışanı arasında anket çalışması yapıldı. Çalışmanın ilk bölümü iş tatmini, örgütsel bağlılık ve beş liderlik davranışını ölçen araçların faktör analizinden oluşmaktadır. Kaiser-Meyer-Olkin (KMO) testi ve Bartlett Küresellik Testi çalışma örnekleminin faktör analizine uygun olduğunu göstermiştir. İkinci bölümde çok değişkenli regresyon modeli ve tek değişkenli analiz yer almaktadır. Katılımcı özelliklerine ve ölçeklere ilişkin tanımlayıcı istatistikler ortalama, standart sapma, frekans ve yüzde ile sunuldu. İstatistiksel anlamlılık 0,05 düzeyindeydi. İş memnuniyetini ve örgütsel bağlılığı tahmin etmek için çok değişkenli regresyon modelleri uygulandı. Açıklayıcı değişkenler katılımcı özellikleri ve bağımlı değişkenlerle istatistiksel olarak anlamlı bir ilişkiye sahip olduğu tespit edilen liderlik davranışlarıdır. Sonuç olarak sağlık kurumlarında çalışan personelin örgütsel bağlılığının görev odaklı lider ve insan odaklı lider kavramlarıyla ilişkili olduğu araştırma bulgularımız ile desteklenmektedir. Anahtar Kelimeler: İş tatmini, Liderlik, Örgütsel bağlılık, Sağlık çalışanı.
Sağlık Kurumu Yöneticilerinin Liderlik Tarzlarının Sağlık Çalışanlarının İş Tatmini ve Örgütsel Bağlılıkları Üzerindeki Etkileri
Keywords: Health professional; Job satisfaction; Leadership; Organizational commitment; İş tatmini; Liderlik; Örgütsel bağlılık; Sağlık çalışanı